Qatar’s Foreign Aid Policy: Evolution, Motives and Values - Fadhl A. Bashir; Elfatih Abdelsalam (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
This paper presents pertinent aspects of the foreign aid policy of the State of Qatar as a Muslim emerging donor with rising soft power. The study traces and explains the evolution of Qatar’s Foreign Aid Policy (QFAP) and identifies the various critical milestones of the policy that has been successfully transformed from a small Gulf Emirate into one of the leading players on both regional and global issues including aid giving. Although, Qatar’s motivation for aid giving is quite similar to the global setting, the country’s sociocultural background and values play a vital in shaping and inspiring its aid policy. As QFAP is closely tied to the country’s active foreign policy agenda, political and security motives are heavily reflected in the country’s aid practices. In collecting both primary and secondary data this study used various qualitative methods such as face-to-face interviews with key Qatari officials and scrutinized official state documents and quoted speeches, particularly of past and present Emirs as well as other archival sources.